Diastereoselective Carbamate Annulation for the Synthesis of 2, 5‐Dideoxy‐2, 5‐iminoglycitols. Issue 26 (13th September 2017) - Hunt‐Painter, Alex A.; Moggré, Gert‐Jan; Tyler, Peter C.; Stocker, Bridget L.; Timmer, Mattie S. M.
Abstract: A combination of the Vasella‐reductive‐amination and carbamate annulation reactions was applied on a ketose starting material for the diastereoselective total synthesis of 2, 5‐dideoxy‐2, 5‐imino‐glycitols. The synthesis of 2, 5‐dideoxy‐2, 5‐imino‐l ‐iditol (4 ) was particularly expedient (6 steps and 18% overall yield) as the route minimises the use of protecting groups, thereby reducing the number of synthetic steps and increasing the overall yield. The Vasella reductive amination methodology could be readily applied to the amination of ketones, albeit with moderate diastereoselectivity. However, the I2 ‐mediated carbamate annulation strongly favours the formation of pyrrolidines with the 2, 5‐ trans and 4, 5‐ cis relationships. The highly diastereoselective carbamate annulation thus provided a general means by which to synthesise 2, 5‐dideoxy‐2, 5‐imino‐glycitols of defined stereochemistry. Abstract : The total synthesis of 2, 5‐dideoxy‐2, 5‐imino‐L‐iditol was achieved in 6 steps and 18% overall yield from readily availabled ‐fructose. Key in this synthesis was the development of the Vasella‐reductive‐amination and carbamate annulation of a ketose starting material, allowing for minimal use of protecting groups to minimise the number of synthetic steps and increase overall yield.